2016
DOI: 10.1038/srep22376
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic colloid filtration

Abstract: Filtration of natural and colloidal matter is an essential process in today’s water treatment processes. The colloidal matter is retained with the help of micro- and nanoporous synthetic membranes. Colloids are retained in a “cake layer” – often coined fouling layer. Membrane fouling is the most substantial problem in membrane filtration: colloidal and natural matter build-up leads to an increasing resistance and thus decreasing water transport rate through the membrane. Theoretical models exist to describe ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
52
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 18 publications
2
52
0
Order By: Relevance
“…Clogging is encountered at many length scales, ranging from the deposition of marginally-soluble asphaltenes at pipe walls in oil recovery1, the formation of protein fouling layers in waste water treatment23, particle clogging during membrane filtration4 or microfluidic operations567. Similar phenomena are encountered at much larger length scales such as in blockades of granular hopper flows8, the emergence of traffic jams on merging lanes910 or in crowds swarming through narrow escape routes1112.…”
mentioning
confidence: 99%
“…Clogging is encountered at many length scales, ranging from the deposition of marginally-soluble asphaltenes at pipe walls in oil recovery1, the formation of protein fouling layers in waste water treatment23, particle clogging during membrane filtration4 or microfluidic operations567. Similar phenomena are encountered at much larger length scales such as in blockades of granular hopper flows8, the emergence of traffic jams on merging lanes910 or in crowds swarming through narrow escape routes1112.…”
mentioning
confidence: 99%
“…Fouling by colloidal particles remains a major issue in many industrial processes including particle synthesis and solid handling in microreactors, membrane filtration, and liquid chromatography, often leading to complete stoppage of the process [1]. Even though this clogging issue is specific to each application, some generic features have been identified thanks to the use of microfluidic technology coupled with various imaging techniques such as confocal microscopy [2][3][4][5][6][7]. This technology enables the design of microdevices with complex geometries [8] that mimic industrial processes, in particular membrane filtration, and inside these devices we can follow the capture or deposition of colloidal particles over time, at the pore scale level, using diverse microscopy techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have determined the influence of pore geometry (width, shape, length, varying or fixed cross section) [3,5,[9][10][11], the confinement, i.e. the ratio between the particle radii and the smallest dimension of the pore [4,5,10], the polydispersity of the colloidal suspensions [12,13], the stability of the suspension with respect to the DLVO interaction potentials, between particles and the pore walls and between particles themselves [3][4][5][14][15][16], and the deformability of the particles [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, concentration polarization becomes a serious drawback in microfluidic membrane filtration. As in conventional macroscale filtration, membrane fouling is also a factor to be considered when designing a microfluidic filtration system [33][34][35]. In previous studies [36,37], it was demonstrated that, with a micromixer incorporated with a microfluidic membrane filtration system, the permeate flux could be significantly improved via chaotic mixing that reduces the amount of fouling on membrane surfaces.…”
Section: Introductionmentioning
confidence: 99%